MODEL SIMULASI INTERAKSI GELOMBANG DAN ARUS DUA DIMENSI - SUJANTOKO
The extended mild-slope equations have been derived by Kirby (1986) can be applied on simulation of wave transformation from deep water to coastal. It's developed Kirby's model with considering current factor. The effect of current on wave transformation have been modeled with finite difference methods. This model can be applied only on one coordinate follow the dominant wave direction, but it can be apllied to different angles wave on the same computational grid. According to verification of numerical models and analitical model, the difference of mean longshore current velocity less than 5%. It means that this numerical model provide good simulation of current caused by wave induction. Verification of wave model on Johnson (1952), Wiegel (1962), and Wei, G. (1998) result similarity. But there is still any difference because this model considering current factor. To evaluate it's reliability, this numerical model tested on case of flow through obstacle dan submerged structure. The result shows that shoaling, refraction, difraction and breaking influence incident wave direction, wave height, surface water elevation and current. Based on simulation model, the effects of current on wave height and surface water elevation about 5-20%. Therefore, it must be considered on coastal structure planning.